KOBLEN PRISON MUSEUM AS AN EMBODIMENT OF HISTORICAL INTERPRETATION NARRATIVES BASED ON PEIRCEAN SIGN SYSTEM IN SURABAYA - Arda Cahyo Pranowo; Hari Purnomo; Josef Prijotomo (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2012)
Historical interpretation on the site of cultural heritage as a series of signs could be used as a channel for creativity in architectural design. History was a subjective interpretation from personal view that had been documented or published to the public. This thesis is looking for the narratives that had been presented within former Koblen Prison as a specific case study so it could be used to produce design criterias for the new facilities. The brief research process was involving document findings, site exploration, and evidence gathering. After all related evidences have been collected, the next activity was a critical analysis of the story with logical argumentation. Categorization should be done to simplify the complexities that arise so that it can be applied appropriately to the architectural expression. Each category was then studied based on signs according to Peirce's trichotomy so that may explain the relation of meaning that emerged from the the observer’s point of view. Peirce’s approach was in a semiotics discourse that had different scope from architecture discourses but it would be useful for understanding the meaning and their connections. The stories that appear on the site consists of three main stories. The stories include the story of the struggle for independence, the story of prison life, and the story of architectural transition. Museum was the new facility that was expected to be the solution to the problem of abandoned cultural heritage sites in the former Koblen Prison in Surabaya. The main result of the research was a museum design study that communicates with the observer about the site’s pasts and respects the site’s contexts through architectural expressions.